Tree-crop interaction - A sustainability issue in agroforestry: A review - Doddabasawa, Doddabasawa; Chittapur, B M (Indian Journal of Agroforestry, 2023)
In recent times trees on farm land are gaining considerable attention worldwide since trees provide ecosystem services besides imparting sustainability to agriculture while improving ecosystem. However, complexity of agroforestry systems and the competitive interactions are the major challenges in optimizing system productivity. Trees influence associated field crops either negatively or positively depending on management and prevailing ecological situation, and understanding these processes though difficult but is most essential from growers point. Extent of these effects depends on tree species, climate and soil which progressively change over time with age, size and density of tree species and corresponding response of crops forming the system. Understanding, particularly the extent of competitive zone influencing cropping is essential for determining tools, technologies and management practices to improve the productivity of the system as a whole. Under normal circumstances compact or erect canopy, deep rooting with a few lateral roots, deciduous and nitrogen fixing trees are promising.Further, the orientation of trees with regard to solar insolation assumes significance depending on altitude and/or latitude.Â  Generally, East-west tree lines should be preferred in lower latitudes (500). Competition under tree canopy would be higher and it decreases as the distance increases from the tree line, and the optimum distance depends on tree species, its age, height and the nature of associated crop. The competitive zone mostly spreads up to 1.5 to 2 times the tree height and would be changing with advancement in tree growth. In field crops, C3 species particularly the shade tolerant crops such as turmeric, ginger, colocasia etc. with underground economic part fared well. In all, the competitive effects when managed may still reduce the yield by 10 to 15 per cent which could well be compensated by tree component.